Evolutionary game analysis of carbon emission reduction in transportation infrastructure construction under dual regulation - Yinghui Zhang; Yun Chen (Heliyon, 2024)
Under the dual regulation of government intervention and environmental constraints, user demand, low-carbon awareness, and the willingness of construction enterprise to reduce carbon emissions are crucial to the realization of low-carbon transportation infrastructure construction. Basing on prospect theory, this paper constructs an evolutionary game model for the government, construction enterprise, and user, explores the stabilization of the three-game players' strategy choices, and discusses the influence of key parameters on the behavior evolution of relevant players through simulation analysis. The results indicate that: the regulatory cost when the government adopts incentives or no incentives is an important factor affecting the strategy choice. The enhancement of incentives by the government can promote the construction of enterprise and the selection of low-carbon transportation infrastructure by user. However, when the benefit of government credibility outweighs the incremental cost of household subsidies, carbon subsidies, and regulation, the government changes its strategy and no longer adopts encouraging strategy. Improving benefits of build low-carbon transportation infrastructure reducing incremental costs, setting a ladder carbon tax rate, increasing carbon tax rate for traditional construction, and decreasing for low-carbon construction is an effective approach to stimulate enterprise to construct low-carbon transportation infrastructure. The user's choice of low-carbon transportation infrastructure strategy is positively correlated with the subsidy received and is less affected by environmental benefits. And the construction enterprise's strategy choice hasn't been influenced by user, which is related to the public service characteristics of transportation infrastructure.